(untitled) (Journal of International Studies, 2024)
The Indo-Pacific region has emerged as a significant global focal point due to the increasing influence exerted by China and the United States. In light of the dynamic nature of the global geopolitical landscape, Malaysia and Indonesia, as two prominent Southeast Asian states, find themselves at the nexus of this competition. China and the United States are two regional superpowers which have strategically positioned themselves in the Indo-Pacific. A systematic literature review was conducted to examine the crucial role of Indonesia and Malaysia in the context of the escalating Sino-US strategic competition in the Indo-Pacific region. By focusing on research articles, books and reports, this work explored the policy and strategic outlook, methodological approaches and methods underpinning Indo-Pacific discourse in Indonesia and Malaysia. The methodology adopted for this review was systematic by following the seven stages suggested by Petticrew and Roberts (2008). This review’s findings indicated the diverse range of theories, methodologies, practical strategies, and approaches that scholars have employed in examining the roles of Indonesia and Malaysia in the Indo-Pacific region. Consequently, this paper broadens the scope for scholars by expounding upon the strategic outlook of Indonesia and Malaysia within the Indo-Pacific discourse, along with the various methodological and theoretical frameworks and conceptual models that may inform future research endeavours. This study was however, limited to gathering input from journal articles, books, book chapters, and reports, and excluding other sources such as conference papers and op-eds. Furthermore, the scope of studies accessed was limited to data available from 2013 to September 2023.